Titulacao do sevoflurano utilizando o indice bispectral em anestesia pediatrica. Influencia da medicacao pre-anestesica no tempo de despertar e no consumo de anestesico inalatorio - Ganem, Eliana Marisa [UNESP]; Módolo, Norma Sueli Pinheiro [UNESP]; Vianna, Pedro Thadeu Galvão [UNESP]; Castiglia, Yara Marcondes Machado [UNESP] (My University, 2000)
Background and Objectives - Sevoflurane is an inhalational anesthetic drug with low blood/gas solubility providing fast anesthesia induction and emergence. Its ability to maintain cardiovascular stability makes it ideal for pediatric anesthesia. The aim of this study was to evaluate hemodynamic stability, consumption of inhalational anesthetics and emergence time in children with and without premedication (midazolam or clonidine) anesthetized with sevoflurane titrated according to BIS monitoring. Methods - Participated in this study 30 patients aged 2 to 12 years, physical status ASA I, undergoing elective surgeries who were divided into 3 groups: G1 - without premedication, G2 - 0.5 mg.kg-1 oral midazolam, G3 - 4 μg.kg-1 oral clonidine 60 minutes before surgery. All patients received 30 μg.kg-1 alfentanil, 3 mg.kg-1 propofol, 0.5 mg.kg-1 atracurium, sevoflurane in different concentrations monitored by BIS (values close to 60) and N2O in a non rebreathing system. Systolic and diastolic blood pressure, heart rate, expired sevoflurane concentration (EC), sevoflurane consumption (ml.min-1) and emergence time were evaluated. Emergence time was defined as time elapsed between the end of anesthesia and patients' spontaneous movements trying to extubate themselves, crying and opening eyes and mouth. Results - There were no differences among groups as to systolic and diastolic blood pressure, EC, sevoflurane consumption and emergence time. Heart rate was lower in G3 group. Conclusions - Sevoflurane has provided hemodynamic stability. Premedication with clonidine and midazolam did not influence emergence time, inhaled anesthetic consumption or maintenance of anesthesia with sevoflurane. Anesthesia duration has also not influenced emergence time. Hypnosis monitoring was important for balancing anesthetic levels and this might have been responsible for the similarity of emergence times for all studied groups.
Titration of sevoflurane using the bispectral index in pediatric anesthesia. Premedication effects on emergence time and consumption of inhalational anesthetic
Keywords: ANESTHETICS, Volatile: sevoflurane; MONITORING: electroencephalography, bispectral index; PREMEDICATION: clonidine, midazolam; alfentanil; atracurium; clonidine; midazolam; nitrous oxide; propofol; sevoflurane; anesthesia induction; anesthetic recovery; child; clinical article; controlled study; dose response; drug effect; electroencephalography; female; heart rate; hemodynamics; human; male; patient monitoring; pediatric anesthesia; premedication; titrimetry